Comparing the place of experts during the first waves of the COVID-19 pandemic (Stockholm University Press, 2024)
The health crisis the world is going through is arguably the first contemporary “global crisis” that threatens the world with generalized anomy and its new economic option, globalization. It has struck China, settles in Europe, strikes heavily in the United States and Latin America, and is spreading rapidly in other continents. The same problem has to be faced by different States and it addresses fascinating questions to social and political sciences. To understand, we must compare said political scientist Giovanni Sartori. Comparing the way in which States are managing this crisis can allow us to understand the global crisis and the national specificities. The first reaction of the States is a considerable predilection for sanitary methods of quarantine and containment. The aim is to understand the effects of this crisis on every political system and every legal system. How were the actions taken, received, approved or challenged? How do different national political cultures adapt to new situations? What does this tell us about each of the societies, about each of the political regimes and, ultimately, about the place of the State in contemporary societies? Are the legal instruments one of the means to manage the crisis? Is the organization of the State reinforced or weakened in the context of the health emergency? What do these levers tell us about the metamorphoses of the contemporary State in a period of unprecedented health crisis? Since April 2020, a new research network in political science, discourse analysis and law has been established on the consequences of the COVID-19 pandemic on the States (Posoc19, Pouvoirs et Sociétés Face à la Crise du COVID-19). The objective of the current project is to focus on the axis of expertise in order to empower the network and be able to compare the ways in which political systems are based on scientific expertise. To what extent is political power based on scientific expertise? Is the expertise autonomous? What is the effect of expertise on public opinion? How does it help to fight against the spread of fake news? A research group inside the network Posoc19 has been established in May 2020 and focuses on the comparison of experts' profiles and discourses. During the spring of 2020 and during the COVID-19 pandemic, new expert figures emerged in connection with public health issues. In some countries, official expert figures have even imposed themselves in order to be able to legitimize the decisions taken by the political authorities, while in other countries, there has been more visibility of conflicts of expertise involving experts appointed by political power (sacralization of the expert who in this case assumes a political function, with or without political responsibility to bear) versus university experts and researchers. In addition, the media have sometimes selected certain experts for other reasons (proximity to lobbies, in particular pharmaceuticals, political and / or partisan positions, relations with a cabinet or a company, etc.), which made the situation even more complex. In some cases ""super experts"" have emerged, in others more collegial formats have been chosen. Some countries opted for mixed strategies with a combination of superexperts and committees. In addition to the fundamental question of the choice of experts (on a political, scientific, media, etc. basis) there has also been the question of political responsibility for the choices made, both in the short and in the long term. The gradual shift to a slower time frame (after the first few weeks in an emergency) makes it possible to ask questions and offer an analysis of different national cases, especially when economic imperatives seem to be taking over. It is also important to know if the experts influenced incumbent politicians on the choice of a strategy or if it was the strategy that made politicians choose the experts. The analysis of public policies is relevant here in order to compare the actors (experts / committees / government / administration /politicians), the agenda and the nature of the decision. The final aim of the research is to produce an accurate typology of systems of expertise due to the comparative approach.